The Economic and Fiscal Impact of Influenza Vaccination for Health Care Workers in Italy - Giovanna Elisa Calabrò; Filippo Rumi; Elettra Fallani; Roberto Ricciardi; Americo Cicchetti (Vaccines, 2022)
Influenza has a significant impact on the health care system and also on production and economic systems. Vaccinated health care workers (HCWs) are more likely to have improved productivity compared to unvaccinated workers. The study aim was to estimate the economic and fiscal impact of an influenza vaccination program for HCWs in Italy. We performed a cost analysis aimed to estimate the indirect costs (productivity losses due to working days lost) and the increase in tax revenues derived from the increase in vaccination coverage among HCWs. Assuming an incremental increase in vaccination coverage of 10% per year over a period of 5 years, total savings could be obtained in terms of a reduction in productivity losses equal to −€4,475,497.16 and an increase in tax revenues of €327,158.84. This revenue could be used to finance other health interventions. Our results are fundamental in view of the sustainability of health systems and of a value-based allocation of health resources. Therefore, a complete social perspective, including the fiscal impact of flu vaccination, should be adopted to assess the economic value of influenza vaccines. Currently, health policies based on the whole value of flu vaccination are needed.